Penerapan Analisa Tingkat Kepuasan dan Kualitas Pengguna terhadap Aplikasi Balindo dengan Metode Webqual 4.0 dan IPA - Gifty Mathilda Zefanya; Tri Santoso; Syahriani Syahriani (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
In analyzing the level of user satisfaction and quality on the Balindo application and evaluating the influence of users after they have experience in using the Balindo application by applying the WebQual 4.0 method and the IPA method. Researchers collected data by distributing questionnaires made for users, namely customers/tenders from Balindo application users totaling 250 people. When the questionnaire data has been collected and after processing the data, the results of the process can be seen from the validation test R Calculation> R Table. This reflects that the question items from the questionnaire have a significant correlation to the total score or can be declared valid. After that, the results of the reliability test can be obtained from the results of the Cronbach's Alpha value of all items> 0.06. From this, it can be said that the questionnaire items are reliable or consistent, so they can be used as a data collection tool to carry out research and cover the division of priorities in order to get a very important response and must still be considered. After calculating the quality and user satisfaction of the Balindo application, the results of the interpretation showed that many respondents felt satisfied with the alternative of auctions as they usually do but have a significant influence on the potential for errors or mistakes in the Balindo application so that this can be used as evaluation material and further development of the Balindo application to make it even better.